A Nonlinear Attitude Controller for a Launch Abort System of a Manned Spacecraft - Ghasem Kahe; Maysam Mohammadi-Amin; Arash Sefidan Benisi (فصلنامه علوم و فناوری فضایی, 2017)
Various strategies have been developed to increase the safety of spacecraft crews, among which the Launch Abort System has been widely considered by the space centers across the world. The launch abort system should be able to carry the crew module away from the failed launcher or rocket in a short time in accordance with the predetermined profile and recover the crew module on the ground. While the main part of the vehicle flight consists of the tracking, reorientation, and settling phase; attitude control in the flight path is done via the roll and pitch channel. Non-linear dynamic inversion flight control is considered for the attitude control of the LAS. Tracking the predetermined profile for the angle of attack as well as the sideslip angle and maintaining the stability of the vehicle in the flight path are considered as the control objectives based on the requirements. Simulations and analytical evaluations indicate the outperformance of the proposed controller for the attitude control of LAS in line with the predetermined profile.